A Chromosome-level genome assembly of the alpine medicinal plant Bergenia purpurascens (Saxifragaceae) - Xue-Die Liu; Alex D. Twyford; Peter M. Hollingsworth; Ya-Huang Luo; Sheng-Ping Ming; Bo-Yun Yang; Lian-Ming Gao; Shao-Lin Tan (Scientific Data)
Abstract Mountain ecosystems harbor high levels of biodiversity, but the genetic mechanisms underlying adaptation to harsh alpine conditions remain largely unknown. Bergenia purpurascens (Saxifragaceae) is an important alpine endemic species of the Himalaya-Hengduan Mountains (HHM), with this species being used as a source of medicine and as an ornamental plant. In this study, we generated a high-quality genome assembly comprising scaffolds representing the 17 chromosomes, with a total length of 650.70 Mb and a scaffold N50 of 34.19 Mb. A total of 45,841 protein-coding genes were annotated, and 10,797 noncoding RNAs were identified. Repeat sequences accounted for 56.72% of the genome. The reference genome of B. purpurascens serves as a valuable resource for studying bergenin biosynthesis, and understanding adaptation of plants to alpine environments.